Discourse wars and ‘mask diplomacy’: China’s global image management in times of crisis - Stefan Müller; Samuel Brazys; Alexander Dukalskis (Political Research Exchange)
To achieve foreign policy goals and boost prestige, states try to influence how foreign publics perceive them. Particularly during crises, the imperative to mitigate a negative image may see states mobilize resources to change the global narrative. This paper investigates whether China’s ‘mask diplomacy' efforts influenced portrayals of the country in the early days of the Covid-19 pandemic. We validate and apply a semi-supervised scaling method to 1.5 million English statements in newspapers around the world mentioning China and Covid-19. Multi-period difference-in-differences models reveal that media tone improved significantly after mask diplomacy engagement. Using its Covid-19 White Paper to determine China’s preferred external narratives, we also find that a country’s domestic media reproduced key terms more after the country received PRC support.